2010
DOI: 10.4028/www.scientific.net/amm.24-25.115
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Planar Cruciform Specimen for Biaxial Characterisation of Polymer Matrix Composites

Abstract: This paper details work undertaken towards the development of a standard test method for the biaxial response of planar cruciform specimens manufactured from carbon fibre-reinforced plastic (CFRP) laminates and subject to tension-tension loading. Achieving true biaxial failure in a cruciform specimen without the need for the inclusion of a stress raiser, such as a hole, in the gauge-section, is a subject attracting much research globally and is by no means a trivial exercise. Coupon designs were modelled using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…However, tubular specimens are not representative of typical laminated composite materials coupon specimens or structures which are flat/planar or display a large curvature radius compared with the laminate thickness, and where the arrangement of reinforcement fibres is ply-wise discretely discontinuous. For that reason, cruciform specimens often have been chosen [4][5][6][7][8][9] to characterise the biaxial mechanical performance of composite laminates for biaxial tensiontension, tension-compression and compression-compression loading. Successful testing of cruciform specimens requires extensive and careful machining of the specimens to create a reduced gauge section thickness and a corner fillet to prevent premature failure outside the gauge section.…”
Section: Introductionmentioning
confidence: 99%
“…However, tubular specimens are not representative of typical laminated composite materials coupon specimens or structures which are flat/planar or display a large curvature radius compared with the laminate thickness, and where the arrangement of reinforcement fibres is ply-wise discretely discontinuous. For that reason, cruciform specimens often have been chosen [4][5][6][7][8][9] to characterise the biaxial mechanical performance of composite laminates for biaxial tensiontension, tension-compression and compression-compression loading. Successful testing of cruciform specimens requires extensive and careful machining of the specimens to create a reduced gauge section thickness and a corner fillet to prevent premature failure outside the gauge section.…”
Section: Introductionmentioning
confidence: 99%
“…In strength calculations, patterns based on assumptions are commonly used, although they are rarely practically met. More general bending descriptions are known that do not depart from these assumptions, but the benefits of their practical use are generally small compared to the complexity of the calculations they cause [6][7][8]. Flexural strength is a conventional quantity.…”
Section: Fig 4 Scheme Of Considered Systemsmentioning
confidence: 99%
“…Makris et al [14] and Makinde et al [4] optimized the specimen shape by a numerical optimization technique with a parametric finite element model. Lamkanfi et al [15] and Gower and Shaw [16] showed that geometrical discontinuities like the transition zone to the tapered thickness area have a major influence on the strain distribution leading to premature failure. Serna Moreno et al [17] compared specimens with arms of different widths for chopped glass-reinforced polyester.…”
Section: State-of-the-artmentioning
confidence: 99%